Pseudo-Richard van Saint-Victor: Profiel van een anonymus. Een onderzoek naar bronnen, context en strekking van het Tractatus super Cantica canticorum - Reynaert, Joris (Ons geestelijk erf, 2024)
In 1943, Johanna Marie Schalij published an article in Tijdschrift voor Nederlandse Taal- en Letterkunde in which she demonstrated that the commentary on the Song of Songs traditionally attributed to Richard of St. Victor must have served as the source for Hadewijch’s Tenth Letter. This commentary — whose attribution to Richard has since been withdrawn — has played a significant role in scholarly discussions regarding the dating of Hadewijch’s works and the relationship between her Tenth Letter and a corresponding excerpt in the Limburg Sermons. A thorough examination of the manuscript tradition of Pseudo-Richard’s commentary, along with its Middle Dutch translations — findings that I previously published in Ons Geestelijk Erf — led me to conclude that Hadewijch herself must have been the (adapting) translator of this excerpt and that her translation constitutes the earliest known witness to the existence of the Latin text. In this article, I continue my search for chronological markers while also considering the broader historical context. My aim is to construct a profile of the author of the commentary by analysing his engagement with earlier and contemporary interpretations of the Canticle, his selection of sources, and the insights his text provides regarding its implied author and intended audience. With respect to the commentary’s exegesis of the Canticle, Pseudo-Richard demonstrates considerable erudition, likely acquired through extensive engagement with preceding commentaries as well as encyclopaedic compilations — most notably the Expositio in Cantica canticorum by Honorius Augustodunensis. The Tractatus super Cantica canticorum, as it is consistently titled in the manuscripts, is clearly indebted to the mystical traditions of twelfth-century northern France. However, it distinguishes itself through its pronounced emphasis on the ethical dimensions of the soul’s relationship with God, highlighting devotion, virtuous deeds, and obedience to divine command. This strong ethical focus underscores an active engagement with the external world and a concern for the lay community, to which the Bride is exhorted when her Beloved commands her to 'arise' and seek Him — both at the beginning and at the conclusion of the passage selected for the commentary (Cant. 3:1–5:16). In this respect, the Tractatus aligns with what Susan Lavere has identified as 'a particularly apostolic reading of the Song of Songs' in early scholastic literature. In addition to this affinity, Pseudo-Richard appears to have been influenced by university theology, particularly in his treatment of morosa delectatio (‘lingering pleasure, complacent dallying’). The broader dissemination of this concept in religious literature appears to date only from the second half of the thirteenth century, following the Summae of Alexander of Hales, Albert the Great, Bonaventure, and Thomas Aquinas. If a connection between Pseudo-Richard’s work and scholastic literature from around or after 1250 can be established, this would suggest that Hadewijch’s Tenth Letter could not have been composed before the third quarter of the thirteenth century.